Preparation method and application of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon

By introducing nitrogen elements into activated carbon and combining thermal activation method, nitrogen doping-thermal activated composite hydrophobic modified activated carbon was prepared, which solved the problem that activated carbon affects its VOCs adsorption effect by adsorption of water molecules, and achieved more efficient VOCs adsorption Performance and stability.

CN119425624AActive Publication Date: 2025-02-14DALIAN UNIV OF TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411733673.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-14
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

When existing activated carbons adsorb volatile organic compounds (VOCs), due to their strong adsorption ability to water molecules, the adsorption effect is reduced, and the commonly used hydrophobic modification methods are likely to cause damage to the pore structure or high cost.

Method used

By immersing urea to introduce nitrogen elements, combined with thermal activation method, pyrolysis is carried out in an oxygen-free environment of 500-700°C to form nitrogen-doped-thermal activated composite hydrophobic modified activated carbon, which increases its specific surface area and micropore number and reduces the number of cells. Oxygen-containing functional groups improve hydrophobicity.

Benefits of technology

It significantly improves the hydrophobicity of activated carbon and the adsorption selectivity of VOCs, enhances the adsorption effect in high humidity environments, and does not involve toxic and harmful substances, and has relatively low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425624A_ABST
    Figure CN119425624A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of activated carbon material modification, and relates to a preparation method and application of nitrogen-doped-thermal-activated composite hydrophobic modified activated carbon. The method comprises the following steps: pretreating activated carbon; then carrying out dipping treatment on the pretreated activated carbon by using urea dipping liquids with different concentrations, and drying to obtain nitrogen-doped activated carbon; and then carrying out thermal activation on the nitrogen-doped activated carbon in an oxygen-free environment at 500-700 DEG C, and cooling to obtain the nitrogen-doped-thermal-activated composite hydrophobic modified activated carbon. Test data shows that when the relative humidity of the gas is 80%, the saturation adsorption time of the composite hydrophobic modified activated carbon to dichloromethane in the gas can be prolonged by 44.83% compared with unmodified activated carbon, the saturation adsorption capacity is 53.7 mg / g and is increased by 66.65% compared with the unmodified activated carbon, and the composite hydrophobic modified activated carbon can be used for adsorbing dichloromethane in the gas. Active carbon composite hydrophobic modification is beneficial for improving the adsorption selectivity of the adsorbent on VOCs under a high-humidity condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of modified activated carbon materials, and specifically relates to a preparation method and application of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon. Technical Background

[0002] Volatile organic compounds (VOCs) refer to volatile organic compounds with a saturated vapor pressure greater than 70Pa at room temperature and a boiling point of 260°C at normal pressure. They not only pose a threat to human health, but may also cause serious environmental problems such as greenhouse effect and photochemical smog. Therefore, the treatment of VOCs is particularly important. The adsorption method has the advantages of simple operation and low energy consumption, and has firmly occupied the first place in the domestic market. Among them, activated carbon has become one of the most popular adsorption materials due to its good adsorption performance and low price. However, in actual applications, the adsorption effect of activated carbon is greatly affected by water molecules in the exhaust gas. During the adsorption process, water molecules will compete with VOCs molecules for adsorption sites on the surface of activated carbon, resulting in a decrease in the adsorption capacity of VOCs. Therefore, it is necessary to perform hydrophobic modification on the activated carbon to reduce the adsorption of water vapor, thereby improving the adsorption capacity of activated carbon for target VOCs.

[0003] At present, the commonly used hydrophobic modification methods include impregnation method and thermal activation method. The impregnation method usually loads hydrophobic compounds such as organic silane on the surface of activated carbon to achieve the purpose of hydrophobicity, but it is very easy to cause the pore structure of activated carbon to be blocked, which reduces the adsorption performance and regeneration performance of activated carbon, and the cost is relatively high, so it is rarely used in actual production; the thermal activation method treats the activated carbon at high temperature to remove the oxygen-containing functional groups on the surface of activated carbon, reduce its surface polarity, and thus reduce the adsorption amount of water molecules, but it is easy to cause the internal pore structure of activated carbon to collapse, reduce the specific surface area of ​​activated carbon, and is not conducive to the adsorption of VOCs by activated carbon. Summary of the invention

[0004] In view of the shortcomings of the above-mentioned method, the object of the present invention is to provide a preparation method and application of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon.

[0005] The technical solution of the present invention is as follows:

[0006] A method for preparing nitrogen-doped-thermally activated composite hydrophobic activated carbon, comprising the following steps:

[0007] First, urea was introduced into the activated carbon pores by impregnation to prepare nitrogen-doped activated carbon. Then, the activated carbon was thermally activated at 500-700℃ in an oxygen-free environment. The urea crystals in the activated carbon pores were pyrolyzed at high temperature to volatilize NH 3 and CO 2, which is conducive to increasing the specific surface area and the number of micropores of activated carbon, and can improve the problem that the existing thermal activation method may destroy the pore structure of activated carbon and reduce its specific surface area. The activated carbon prepared by this method reduces the oxygen-containing functional groups on the surface of activated carbon and increases the nitrogen content while maintaining a high specific surface area. It can also increase the number of micropores of activated carbon, which can improve the hydrophobicity of activated carbon to a certain extent and improve the selective adsorption of activated carbon to VOCs in a high humidity environment.

[0008] To achieve the above objectives, the present invention adopts the following technical solutions, which are divided into two aspects: preparation and application:

[0009] A method for preparing nitrogen-doped-thermally activated composite hydrophobically modified activated carbon specifically comprises the following steps:

[0010] The first step is the pretreatment of activated carbon: the coal-based columnar activated carbon is repeatedly washed with ethanol and ultrapure water, and dried at 80-110°C;

[0011] The second step is the preparation of nitrogen-doped activated carbon: the activated carbon after the pretreatment is immersed in urea with a mass concentration of 5% to 20%, stirred for 12 to 24 hours, taken out, washed, and placed in an oven at 80 to 110°C for 6 hours to obtain nitrogen-doped activated carbon;

[0012] The third step is the preparation of nitrogen-doped-heat-activated composite hydrophobic modified activated carbon: the nitrogen-doped activated carbon is thermally activated in an oxygen-free environment at 500-700°C, kept warm for 30-120 minutes, and then cooled to obtain the nitrogen-doped-heat-activated composite hydrophobic modified activated carbon.

[0013] Preferably, the first step is drying at 80°C.

[0014] An application of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon specifically comprises the following steps:

[0015] (1) loading an appropriate amount of nitrogen-doped-thermally activated composite hydrophobically modified activated carbon into an adsorption device;

[0016] (2) Control the VOCs concentration to 100-1000 ppm and the relative humidity to 10-80%;

[0017] (3) passing the above-mentioned gas into an adsorption device filled with composite hydrophobic modified activated carbon, controlling the residence time of the gas passing through the activated carbon layer to 0.2 to 1 second, achieving the removal of VOCs in the gas, with a removal rate of more than 90%. The time for the VOCs removal rate to be more than 90% can be controlled by adjusting the activated carbon loading amount, and the replacement or regeneration cycle of the activated carbon can be controlled according to the initial concentration of VOCs in the gas and environmental protection requirements;

[0018] (4) The VOCs concentration in the inlet and outlet gases of the adsorption device is measured in real time by a VOCs analyzer or a gas chromatograph. After the activated carbon is saturated with adsorption, an adsorption penetration curve is drawn to calculate the saturated adsorption amount of VOCs by the composite hydrophobic modified activated carbon.

[0019] The benefits of the present invention are:

[0020] (1) The activated carbon composite hydrophobic modification has a significant improvement effect, and the modification process does not involve the use of toxic and harmful substances;

[0021] (2) It can effectively reduce the content of oxygen-containing functional groups on the surface of activated carbon and increase the number of micropores inside the activated carbon through nitrogen doping-thermal activation, which is beneficial to improving the adsorption selectivity of activated carbon for small molecule VOCs, improving the hydrophobicity of activated carbon and the adsorption effect under high humidity conditions.

[0022] Beneficial effects of the present invention:

[0023] The present invention performs nitrogen doping-thermal activation composite hydrophobic modification on activated carbon. First, the pretreated activated carbon is immersed in urea impregnation liquid, and then it is thermally activated at high temperature. On the one hand, the urea crystals remaining in the pores of the nitrogen doped activated carbon are thermally decomposed into NH 3 and CO 2 Gas, the gas volatilization process will form a microporous structure inside the activated carbon, increase the number of micropores in the activated carbon, and help enhance the selective adsorption of activated carbon to small molecule VOCs; on the other hand, high-temperature thermal activation can effectively remove oxygen-containing functional groups on the surface of activated carbon, reduce the affinity of the activated carbon surface to water molecules, and thus improve the hydrophobicity of activated carbon; in addition, the residual nitrogen elements form nitrogen-containing groups on the surface of activated carbon, increasing the ratio of nitrogen and oxygen elements on the surface of activated carbon (N / O ratio), which is also beneficial to enhance the adsorption performance of activated carbon to VOCs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is a flow chart of the adsorption device used in each embodiment;

[0025] Figure 2 This is a scanning electron microscope comparison diagram of unmodified activated carbon and the composite hydrophobic modified activated carbon in Example 4 of the present invention;

[0026] Figure 3 It is a comparison diagram of pore distribution and specific surface area of ​​unmodified activated carbon and composite hydrophobic modified activated carbon in Example 4 of the present invention;

[0027] Figure 4 It is the adsorption curve of dichloromethane by unmodified activated carbon and the composite hydrophobic modified activated carbon in Example 4 at a relative humidity of 80%.

[0028] In the figure: 1 is N2 gas cylinder; 2 is VOCs / N2 gas cylinder; 3 is flow meter; 4 is H 2 O is a bubbling bottle; 5 is a water bath; 6 is a gas mixing tank; 7 is a hygrometer; 8 is a gas mixing bottle; 9 is an adsorption column. DETAILED DESCRIPTION

[0029] The present invention is further described below by way of examples, but the present invention is not limited to the following examples. The examples are exemplary and intended to be used to explain the present application, but should not be construed as limiting the present application.

[0030] Example 1

[0031] (1) Pretreatment of activated carbon: The activated carbon was repeatedly washed in ethanol solution and ultrapure water, and dried thoroughly at 80°C to remove moisture from the activated carbon and obtain clean and dry activated carbon.

[0032] (2) Preparation of nitrogen-doped activated carbon: The pretreated activated carbon was immersed in a urea impregnation solution with a mass concentration of 5%, and magnetically stirred for 12 hours. Then, the pretreated activated carbon was taken out, washed, and dried in an oven at 110° C. for 6 hours to obtain nitrogen-doped activated carbon.

[0033] (3) Preparation of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon: The dried nitrogen-doped activated carbon was thermally activated in an oxygen-free environment at 500°C for 120 min and cooled to obtain nitrogen-doped-thermally activated composite hydrophobic modified activated carbon.

[0034] (4) The total amount of oxygen-containing functional groups on the surface of the unmodified activated carbon and the composite hydrophobically modified activated carbon in Example 1 was quantified using the Boehm titration method; the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using an X-ray photoelectron spectrometer, and the N / O ratio was calculated; and the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using the X-ray photoelectron spectrometer. Figure 1 The adsorption device shown in the figure tests its dichloromethane adsorption performance and calculates the saturated adsorption capacity of activated carbon for dichloromethane: a certain amount of unmodified activated carbon or nitrogen-doped-heat-activated composite hydrophobic modified activated carbon is loaded into the adsorption device, the gas dichloromethane concentration is controlled to be 1000ppm by a flow meter, the relative humidity is 80%, and the residence time through the activated carbon layer is 0.71s. The dichloromethane concentrations at the inlet and outlet of the adsorption device are recorded by a gas chromatograph and an adsorption penetration curve is drawn to calculate the saturated adsorption capacity of unmodified activated carbon or composite hydrophobic modified activated carbon for dichloromethane. The results are shown in Table 1.

[0035] Table 1 Comparison of main parameters of composite hydrophobic modified activated carbon and unmodified activated carbon in Example 1

[0036]

[0037] Example 2

[0038] (1) Pretreatment of activated carbon: The activated carbon was repeatedly washed in ethanol solution and ultrapure water, and dried thoroughly at 80°C to remove moisture from the activated carbon and obtain clean and dry activated carbon;

[0039] (2) Preparation of nitrogen-doped activated carbon: The pretreated activated carbon was immersed in a 10% urea impregnation solution, magnetically stirred for 12 h, taken out, washed, and dried in an oven at 110° C. for 6 h to obtain nitrogen-doped activated carbon.

[0040] (3) Preparation of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon: The dried nitrogen-doped activated carbon was thermally activated in an oxygen-free environment at 500°C for 120 min and cooled to obtain nitrogen-doped-thermally activated composite hydrophobic modified activated carbon.

[0041] (4) The total amount of oxygen-containing functional groups on the surface of the unmodified activated carbon and the composite hydrophobically modified activated carbon in Example 1 was quantified using the Boehm titration method; the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using an X-ray photoelectron spectrometer, and the N / O ratio was calculated; and the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using the X-ray photoelectron spectrometer. Figure 1 The adsorption device shown in the figure tests its dichloromethane adsorption performance and calculates the saturated adsorption capacity of activated carbon for dichloromethane: a certain amount of unmodified activated carbon or nitrogen-doped-heat-activated composite hydrophobic modified activated carbon is loaded into the adsorption device, the gas dichloromethane concentration is controlled to be 1000ppm by a flow meter, the relative humidity is 80%, and the residence time through the activated carbon layer is 0.71s. The dichloromethane concentrations at the inlet and outlet of the adsorption device are recorded by a gas chromatograph and an adsorption penetration curve is drawn to calculate the saturated adsorption capacity of unmodified activated carbon or composite hydrophobic modified activated carbon for dichloromethane. The results are shown in Table 2.

[0042] Table 2 Comparison of main parameters of composite hydrophobic modified activated carbon and unmodified activated carbon in Example 2

[0043]

[0044] Example 3

[0045] (1) Pretreatment of activated carbon: The activated carbon was repeatedly washed in ethanol solution and ultrapure water, and dried thoroughly at 90°C to remove moisture from the activated carbon to obtain clean and dry activated carbon;

[0046] (2) Preparation of nitrogen-doped activated carbon: The pretreated activated carbon was immersed in a urea impregnation solution with a mass concentration of 20%, and magnetically stirred for 12 hours. Then, the pretreated activated carbon was taken out, washed, and dried in an oven at 110° C. for 6 hours to obtain nitrogen-doped activated carbon.

[0047] (3) Preparation of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon: The dried nitrogen-doped activated carbon was thermally activated in an oxygen-free environment at 500°C for 120 min and cooled to obtain nitrogen-doped-thermally activated composite hydrophobic modified activated carbon.

[0048] (4) The total amount of oxygen-containing functional groups on the surface of the unmodified activated carbon and the composite hydrophobically modified activated carbon in Example 1 was quantified using the Boehm titration method; the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using an X-ray photoelectron spectrometer, and the N / O ratio was calculated; and the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using the X-ray photoelectron spectrometer. Figure 1 The adsorption device shown in the figure tests its dichloromethane adsorption performance and calculates the saturated adsorption capacity of activated carbon for dichloromethane: a certain amount of unmodified activated carbon or nitrogen-doped-heat-activated composite hydrophobic modified activated carbon is loaded into the adsorption device, the gas dichloromethane concentration is controlled to be 1000ppm by a flow meter, the relative humidity is 80%, and the residence time through the activated carbon layer is 0.71s. The dichloromethane concentrations at the inlet and outlet of the adsorption device are recorded by a gas chromatograph and an adsorption penetration curve is drawn to calculate the saturated adsorption capacity of unmodified activated carbon or composite hydrophobic modified activated carbon for dichloromethane. The results are shown in Table 3.

[0049] Table 3 Comparison of main parameters of composite hydrophobic modified activated carbon and unmodified activated carbon in Example 3

[0050]

[0051] Example 4

[0052] (1) Pretreatment of activated carbon: The activated carbon is repeatedly washed in ethanol solution and ultrapure water, and then dried at 100°C to remove moisture from the activated carbon to obtain clean and dry activated carbon;

[0053] (2) Preparation of nitrogen-doped activated carbon: The pretreated activated carbon was immersed in a 10% urea impregnation solution, magnetically stirred for 12 h, taken out, washed, and dried in an oven at 110° C. for 6 h to obtain nitrogen-doped activated carbon.

[0054] (3) Preparation of nitrogen-doped-thermally activated composite hydrophobic modified activated carbon: The dried nitrogen-doped activated carbon was thermally activated in an oxygen-free environment at 700°C for 120 min and cooled to obtain nitrogen-doped-thermally activated composite hydrophobic modified activated carbon.

[0055] (4) The total amount of oxygen-containing functional groups on the surface of the unmodified activated carbon and the composite hydrophobically modified activated carbon in Example 1 was quantified using the Boehm titration method; the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using an X-ray photoelectron spectrometer, and the N / O ratio was calculated; and the relative content of nitrogen and oxygen on the surface of the activated carbon was determined using the X-ray photoelectron spectrometer. Figure 1The adsorption device shown in the figure tests its dichloromethane adsorption performance and calculates the saturated adsorption capacity of activated carbon for dichloromethane: a certain amount of unmodified activated carbon or nitrogen-doped-heat-activated composite hydrophobic modified activated carbon is loaded into the adsorption device, the gas dichloromethane concentration is controlled to be 1000ppm by a flow meter, the relative humidity is 80%, and the residence time through the activated carbon layer is 0.71s. The dichloromethane concentrations at the inlet and outlet of the adsorption device are recorded by a gas chromatograph and an adsorption penetration curve is drawn to calculate the saturated adsorption capacity of unmodified activated carbon or composite hydrophobic modified activated carbon for dichloromethane. The results are shown in Table 4.

[0056] Table 4 Comparison of main parameters of composite hydrophobic modified activated carbon and unmodified activated carbon in Example 4

[0057]

[0058] Comparing Examples 1 to 3, it can be seen that under the same thermal activation temperature, the use of 10% mass concentration of urea impregnation liquid to impregnate activated carbon is conducive to the retention of nitrogen elements, and a higher N / O ratio can be obtained, which is conducive to improving the adsorption performance of activated carbon for VOCs. Comparing Example 3 and Example 4, it can be seen that under the same urea impregnation concentration, when the activation temperature is increased from 500°C to 700°C, the oxygen-containing tube energy groups on the surface of activated carbon can be reduced to a greater extent, and the activated carbon also retains a higher N / O ratio; at the same time, 700°C is more conducive to promoting the thermal decomposition of urea in the activated carbon pores, which is conducive to optimizing the specific surface area of ​​activated carbon and further improving the saturated adsorption capacity of activated carbon for VOCs.

[0059] Figure 2 The scanning electron microscope comparison diagram of unmodified activated carbon and composite hydrophobic modified activated carbon in Example 4 of the present invention is shown. After the nitrogen doping-thermal activation composite hydrophobic modification, the surface texture of the activated carbon becomes darker, and its roughness and etching degree increase, which is conducive to the expansion of the internal pore structure of the activated carbon and the increase of the specific surface area. Figure 3 The pore distribution and specific surface area comparison of unmodified activated carbon and composite hydrophobic modified activated carbon show that the number of micropores with a pore size less than 1 nm increases significantly after composite hydrophobic modified activated carbon. At the same time, the specific surface area of ​​composite hydrophobic modified activated carbon increases from 889.23 m2 before modification to 1.57 m2. 2 / g increased to 918.14m 2 / g, which is due to the thermal decomposition of urea in the activated carbon pores into NH 3 and CO 2 The volatilization process of gas from the activated carbon pores is beneficial to the increase of the specific surface area and the number of micropores of activated carbon. Figure 4This is the adsorption curve of dichloromethane by unmodified activated carbon and the composite hydrophobic modified activated carbon in Example 4 at a relative humidity of 80%. The composite hydrophobic modified activated carbon shows excellent adsorption performance for VOCs under high humidity conditions, and the saturated adsorption capacity is greater than that of unmodified activated carbon. The saturated adsorption time of dichloromethane in the gas can be extended by 44.83% relative to that of unmodified activated carbon, and the saturated adsorption capacity is 53.7 mg / g, which is increased by 66.65% relative to that of unmodified activated carbon.

[0060] In summary, the present invention adopts nitrogen doping and thermal activation method to perform composite hydrophobic modification on activated carbon. First, nitrogen sources such as urea are doped into the activated carbon by impregnation method. Subsequently, the pore structure of the activated carbon is optimized by combining the heat treatment method. The urea in the pores of the activated carbon is decomposed into NH 3 and CO 2 This process is beneficial to the increase of the specific surface area and the number of micropores of activated carbon, which can improve the problem of clogging the activated carbon pores during thermal activation alone. At the same time, thermal treatment can be used to decompose the polar oxygen-containing functional groups on the surface of activated carbon and reduce its surface polarity. The nitrogen-doped-thermally activated composite hydrophobic modified activated carbon finally prepared has good hydrophobicity and stable performance, which helps to improve the adsorption performance of activated carbon for VOCs in high humidity environments.

[0061] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing nitrogen-doped-thermally activated composite hydrophobically modified activated carbon, characterized in that: Here are the steps: The first step is the pretreatment of activated carbon: the coal-based columnar activated carbon is repeatedly washed with ethanol and ultrapure water, and dried at 80-110°C; The second step is the preparation of nitrogen-doped activated carbon: the activated carbon after the pretreatment is immersed in urea with a mass concentration of 5% to 20%, stirred for 12 to 24 hours, taken out, washed, and placed in an oven at 80 to 110°C for 6 hours to obtain nitrogen-doped activated carbon; The third step is the preparation of nitrogen-doped-heat-activated composite hydrophobic modified activated carbon: the nitrogen-doped activated carbon is thermally activated in an oxygen-free environment at 500-700°C, kept warm for 30-120 minutes, and then cooled to obtain the nitrogen-doped-heat-activated composite hydrophobic modified activated carbon.

2. The method for preparing a nitrogen-doped-heat-activated composite hydrophobically modified activated carbon according to claim 1, characterized in that: The first step is drying at 80°C.

3. The use of nitrogen-doped-heat-activated composite hydrophobically modified activated carbon obtained by the preparation method of nitrogen-doped-heat-activated composite hydrophobically modified activated carbon according to claim 1 or 2, characterized in that: The steps include: (1) loading the nitrogen-doped-thermally activated composite hydrophobically modified activated carbon into an adsorption device; (2) Control the VOCs concentration to 100-1000 ppm and the relative humidity to 10-80%; (3) passing the above-mentioned gas into an adsorption device filled with composite hydrophobic modified activated carbon, controlling the residence time of the gas passing through the activated carbon layer to 0.2 to 1 second, achieving the removal of VOCs in the gas, with a removal rate of more than 90%. By adjusting the activated carbon loading amount to control the time when the VOCs removal rate is more than 90%, the replacement or regeneration cycle of the activated carbon can be controlled according to the initial concentration of VOCs in the gas and environmental protection requirements; (4) The VOCs concentration in the inlet and outlet gases of the adsorption device is measured in real time by a VOCs analyzer or a gas chromatograph. After the activated carbon is saturated with adsorption, an adsorption penetration curve is drawn to calculate the saturated adsorption amount of VOCs by the composite hydrophobic modified activated carbon.

4. The use of nitrogen-doped-heat-activated composite hydrophobically modified activated carbon obtained by the preparation method of nitrogen-doped-heat-activated composite hydrophobically modified activated carbon as claimed in claim 3, characterized in that: The VOCs are one or a combination of toluene, ethylbenzene, xylene, dichloromethane, chloroform and chlorobenzene.

Citation Information

Patent Citations

  • Ultralow emission device and method for tail gas dioxin in thermal desorption process of organic contaminated soil

    CN112973351A

  • Organosilane hydrophobic modified activated carbon, preparation method and application thereof

    CN116099505A

  • VOCs treatment system and method based on hydrophobic activated carbon and transition metal

    CN118045455A